Designing Driver Space for Large Car - Zamri, Mohamed (2010)
For the last few decades, three-dimensional human simulation tools have complemented the traditional method of using 2D templates. Human simulation tools are, for example, used for optimizing comfort, fit, reach and vision. In this study, two other methods will be adopted to assist present method of using a 2D SAE template. The other methods will be by measurements and using ergonomic software. Measurement is done by using general layout drawing of benchmark vehicles.. Ergonomic tool that will be used for this study is Ramsis. Anthropometrics data used will be based on 95%tile USA/Canada population and 5%tile Japanese/Korean/Malaysian population. The 95%tile manikin size is used to get the maximum space accommodation while for smaller percentiles will be accommodated with the range of adjustability. Using 5% tile women for the minimum space accommodation, it was found that the SgRP at the most comfortable position for 5% tile women stature is situated lower and toward the front of vehicle. From original SgRP point for 95%tile male, the preferred SgRP point for 5%tile women is 50 mm lower and 200 mm closer to instrument panel. Conclusively, the adjusting range for the seat should be at least 200 mm while it is preferable to have seating height adjustment of 50 mm.